Exploring Basic Arabic Teaching Skills: Innovations in the Era of Artificial Intelligence - Baharuddin, Ismail; Yunaldi, Yunaldi; Larhzizer, Fouad (Arabi : Journal of Arabic Studies, 2025)
In the era of artificial intelligence, mastering basic teaching skills has become increasingly essential for educators, including Arabic language teachers. One of the key competencies is the ability to implement varied instructional strategies to create effective and engaging learning experiences. This study aims to describe the basic teaching skills of Arabic language teachers at Integrated Islamic Private Elementary School 117 Adnani Panyabungan within the context of digital transformation. The research employed a qualitative method with a descriptive approach, collecting data from Arabic language teachers at the school. The findings reveal that teachers applied several forms of instructional variation: (1) variations in teaching methods to maintain students' attention and motivation; (2) variations in the use of media and teaching aids to enhance learning interaction; and (3) variations in interaction patterns and student activities to accommodate diverse learning styles. These findings indicate that the teachers’ basic teaching skills align with theoretical pedagogical standards, enabling them to meet the demands of education in the AI era.